2015
DOI: 10.1088/0004-637x/808/1/27
|View full text |Cite
|
Sign up to set email alerts
|

THE MOLECULAR H2EMISSION AND THE STELLAR KINEMATICS IN THE NUCLEAR REGION OF THE SOMBRERO GALAXY

Abstract: We analyze the molecular H 2 emission and the stellar kinematics in a data cube of the nuclear region of M104, the Sombrero galaxy, obtained with NIFS on the Gemini-north telescope. After a careful subtraction of the stellar continuum, the only emission line we detected in the data cube was H 2 λ21218. An analysis of this emission revealed the existence of a rotating molecular torus/disk, aproximately co-planar with a dusty structure detected by us in a previous work. We interpret these two structures as being… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Galactic nuclei (GNs) can be remarkably rich in molecular gas. An increasing number of observations reveal the presence of circumnuclear gas in the innermost parsecs of nearby GNs, where the gravity is dominated by a supermassive black hole (SMBH, Neumayer et al 2007;Tristram et al 2009;Seth 2010;Davis et al 2013;Menezes et al 2013;Menezes & Steiner 2015;Onishi et al 2015;Barth et al 2016a,b;Onishi et al 2017;Davis et al 2017;Espada et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Galactic nuclei (GNs) can be remarkably rich in molecular gas. An increasing number of observations reveal the presence of circumnuclear gas in the innermost parsecs of nearby GNs, where the gravity is dominated by a supermassive black hole (SMBH, Neumayer et al 2007;Tristram et al 2009;Seth 2010;Davis et al 2013;Menezes et al 2013;Menezes & Steiner 2015;Onishi et al 2015;Barth et al 2016a,b;Onishi et al 2017;Davis et al 2017;Espada et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wylezalek et al 2018); however, the fraction of nuclear activity that is detected may be quite low, since the nebular emission that is powered by AGNs is diluted by the emission that is caused by other ionization processes, mainly because of the lower spatial resolution of the observations (Sánchez 2020). We believe that, with the techniques developed by our group (Steiner et al 2009;Menezes 2012;Menezes et al 2014aMenezes et al , 2015Menezes et al , 2019, together with the high spatial resolution of the DIVING 3D data, we will be able to detect AGNs at lower luminosity limits than the current level of detection. This belief is based on two facts: first, our preliminary results (see Section 4) indicate that we found a significantly higher number of objects with a broad H𝛼 component than anticipated from the Palomar survey.…”
Section: The Scientific Rationalmentioning
confidence: 97%
“…Based on the moderate amount of obscuring materials along the line of sight and their derived small viewing angle of the jet, Hada et al (2013a) suggested that the torus in M104 is nearly face-on, thus classifying it as a type I active galactic nucleus. However, subsequent optical and near-infrared observations by Menezes et al (2013) and Menezes & Steiner (2015) detected a rotating dusty/molecular feature in M104 and interpreted it as a nearly edge-on torus. Assuming that the circumnuclear torus is perpendicular to the radio jets, our results also suggest an edgeon torus.…”
Section: Jet Viewing Anglementioning
confidence: 99%
“…It is located in the Virgo cluster at a distance of 9.55 ± 0.31 Mpc (McQuinn et al 2016) and appears nearly edge-on with an inclination angle of 84°.3 ± 0°.2 (Rubin et al 1985;Sutter & Fadda 2022). Previous optical and near-infrared observations have revealed the presence of an SMBH at its center, with a mass of ∼1 × 10 9 M e (e.g., Kormendy 1988;Emsellem et al 1994;Kormendy et al 1996;Menezes & Steiner 2015). As a result, 1 mas corresponds to a spatial scale of only ∼0.046 pc or 484 R s .…”
Section: Introductionmentioning
confidence: 98%